EFEKTIFITAS PENDIDIKAN DAN PELATIHAN TERHADAP SELLING SKILL, KNOWLEDGE DAN BUDAYA KERJA KARYAWAN BANK ACEH CABANG IDI KABUPATEN ACEH TIMUR PASCA KONVERSI - Zulfadly, Zulfadly; Tarlis, Andi (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2019)
The formulation of the problem in this research is the effectiveness of education and training effect on Selling Skill of employees of Bank Aceh After Conversion amounting to 1220 that is on score